Synthesis and characterization of manganese (IV) oxide - multiwalled carbon nano tubes (MWCNT) composite via solid-state technique / Vicneswaran Arumugam - Vicneswaran, Arumugam (2013)
In this study, -MnO2 (Manganese (IV) Oxide),was hydro thermally synthesized with multi-walled carbon nano tubes (MWCNT) in various mole fractions via solid state technique. FESEM and TEM studies show that the MnO2 layer has covered the surface of the MWCNT while retaining the original structure of the MWCNT during the triturate process. In TEM, the diameter of the MWCNT was found varied from 8 nm to 40 nm. The MWCNT / MnO2 composite diameter however, varied from 30 nm to 120 nm. In XRD analysis based on Sherrer’s calculation, higher mole fraction of MnO2 in the composite increases the crystallite size of MnO2 from 60.71 nm to 91.07 nm. The presence of MnO2 was observed at four distinct peaks (angle 2θ = 28.5o, 37.2o, 56.5o and 59.7o) at planes (110), (101), (211) and (220) respectively. MWCNTs were observed at angle 2θ = 25.8o and 43o, at planes (002) and (100) respectively. The EDX study shows the presence of Mn, O, C in the composite with various weight percentage due to the difference in the composite composition. The impurities such as Al, Si and Fe were found, with less than 5 wt.%. TGA / DTG study shows the thermal stability of the composite increases with higher presence of MnO2. This condition prevents the composite from being easily oxidized and loses weight at higher temperatures. The highest weight loss of the composite was calculated at 45% and the lowest weight loss was calculated at 13 % from the initial weight of the composite. The presence of MnO2 layer over MWCNT has proven to reduce the oxidization of MWCNT. Thus, MnO2 increases the thermal stability of the MWCNT in this composite.